The Interaction of Graphene Oxide with Humic Acids, a Computational Study - Ferlin, Stefan (Jihočeská univerzita, 2020)
This study was focused on the interactions of Graphene oxide with humic acids in aqueous solutions. Additionally, to this work, Graphene oxide and water interactions with and without the addition of ions were studied. The behavior of a fulvic acid in the presence of Graphene oxide has been investigated as well. The study was performed using computer simulations that were achieved by Molecular Dynamics simulations. These simulations provided useful data on a nanometer scale.
The Interaction of Graphene Oxide with Humic Acids, a Computational Study
Keywords: Graphene oxide; Humic acid; Fulvic acid; Hydrogen bridges; Molecular interaction; Aromatic interaction; pi-stacking; Computer simulation; Molecular Dynamics; Graphene oxide; Humic acid; Fulvic acid; Hydrogen bridges; Molecular interaction; Aromatic interaction; pi-stacking; Computer simulation; Molecular Dynamics